Impact of antibiotics as anthropogenic stressor for influencing bacterial evolutionary process – A review - Ghosh, Sanjib (Ecological Questions, 2020)
A large number of human induced stressors are affecting natural evolutionary process through altering ecosystems and biodiversity. Antibiotics are one of the most commonly excreted pollutants released in environment since last eight decades. Antibiotics can alter genetic orientation of bacterial population and can exert selection pressure for emerging new taxon. In environments like soil and water, antibiotics directly or indirectly may affect many aspects of natural systems like biogeochemical cycles, nitrifications and decomposition process. All these may bring new selection pressure for bacteria not only in community or population level but also in species level.